1972
DOI: 10.1113/jphysiol.1972.sp009965
|View full text |Cite
|
Sign up to set email alerts
|

The effect on heart rate of distending the atrial appendages in the dog

Abstract: SUMMARY1. Stretching the atrial appendages in anaesthetized dogs caused an increase in heart rate. This response was unrelated to changes in arterial blood pressure and left and right atrial pressures.2. The increase in heart rate was a reflex response; the afferent path was in the vagi and the efferent solely in the sympathetic nerves.3. The receptors involved in this reflex have been localized to the atrial appendages but there is no conclusive evidence as to their nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 11 publications
2
27
0
Order By: Relevance
“…A third balloon was inserted into the left atrial appendage (Kappagoda et al 1972). A cannula (PE 260, Intramedic, Pasipanny, NJ, U.S.A.) was inserted into the atrium through the appendage so as to record the atrial pressure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third balloon was inserted into the left atrial appendage (Kappagoda et al 1972). A cannula (PE 260, Intramedic, Pasipanny, NJ, U.S.A.) was inserted into the atrium through the appendage so as to record the atrial pressure.…”
Section: Methodsmentioning
confidence: 99%
“…The chemoreceptors were stimulated by perfusion of the isolated carotid bifurcations with venous blood and atrial receptors by localized stretch of the pulmonary vein-atrial junctions (Ledsome & Linden, 1964) and the atrial appendage (Kappagoda, Linden & Saunders, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been shown to stimulate left atrial receptors (Kidd, Ledsome & Linden, 1978) and has enabled Linden and his colleagues to define the reflex effects of stimulating such receptors in the anaesthetized dog. Stimulation of these receptors results in a reflex tachycardia (Furnival et al 1971) and an increase in urine flow (Ledsome & Linden, 1968) but no consistent changes in arterial blood pressure (Ledsome & Linden, 1964), peripheral resistance (Carswell, Hainsworth & Ledsome, 1970) or the pattern of breathing ) Subsequent work has shown that the distension of the atrial appendages (Kappagoda, Linden & Saunders, 1972b) and the junctions between the venae cavae and the right atrium (Kappagoda, Linden & Snow, 1972 a) also results in an increase in the heart rate.…”
Section: Introdtictionmentioning
confidence: 99%
“…A quantitative analysis of atrial natriuretic peptides (ANP) contained in excised LAAs revealed a content of approximately 30% of all cardiac ANP (Chapeau et al, 1985). Experimental studies have demonstrated that infusion of fluid in the LAA result in increased heart rate, diuresis and natriuresis; this further supports a significant role of the LAA in regulating normal cardiac physiology (Kappagoda et al, 1972a, Kappagoda et al, 1972b. The LAA has a distinct pattern of contraction, and shortens to a greater extent than the rest of the left atrium.…”
mentioning
confidence: 77%